Ռուս-թուրքական մրցակցություն, թե՞ համագործակցություն - Թորոսյան, Տիգրան; Արշակյան, Գրիգոր (“Center of Perspective Researches and Initiatives” of the Scientific State Committee (Ministryof Education and Science, RA))
Հոդվածում քննարկվում են հատկապես ռուս-վրացական հնգօրյա պատերազմից հետո կտրուկ վայրիվերումներով աչքի ընկնող ռուս-թուրքական հարաբերութ- յունները: Դրանց տնտեսական բաղադրիչի տպավորիչ աճը և էլ ավելի ընդլայնվելու հեռանկարները երաշխիք չեն դառնում անգամ տեսանելի ապագայում հարաբերությունների կանխատեսելիության ապահովման համար: Վերջին տասնամյակում նոր աշխարհակարգի ձևավորմամբ պայմանավորված Եվրասիական կենտրոնում ծավալվող բուռն զարգացումներով է մեծապես պայմանավորված այդ հարաբերությունների տուրբուլենտային բնույթը: Այդ երկրների հարաբերություններում զգալի ազդեցություն ունի այն հանգամանքը, որ նրանց շահերը համընկնում է դեպի Եվրոպա էներգակիրների տեղափոխման նպատակով իրագործվող որոշ ծրագրերում: Հարաբերությունների բարդությունն ու բազմագործոնությունը հաճախ պատճառ է դառնում համագործակցության կտրուկ վերափոխմանը մրցակցության, իսկ երբեմն էլ՝ կոշտ հակադրության։ The article is focused on the Russian-Turkish relations marked by drastic ups and downs particularly after the Five-Day War between Russia and Georgia. The impressive growth of their economic component and the prospects for further expansion are not a guarantee for predictability of bilateral relations in the foreseeable future. Over the past decade, the turbulent nature of these relations is mostly driven by the rapid developments in the Eurasian Heartland conditioned by new world order formation. Meanwhile, it is also largely due to the clash of interests between Russia and Turkey in the South Caucasus and the Middle East. The relations of the two countries are also affected by the fact that their interests coincide in some projects regarding the transportation of energy resources to Europe. The complex and multifactor nature of their relationship often leads to a drastic transformation of cooperation into rivalry and sometimes even to harsh confrontation, and vice versa.
Keywords: Աշխարհաքաղաքական մրցակցություն